2021
DOI: 10.1002/jsfa.11194
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' attitudes towards GM crops and their predictors

Abstract: BACKGROUND: Genetically modified (GM) crops have become a controversial global issue since their commercialization in 1996. However, despite technological advancements, only a few studies have investigated farmers' attitudes towards GM crops in Malaysia. Therefore, this study aims to analyse such attitudes and their determining factors. A validated questionnaire was distributed to farmers in the Cameron Highlands, Pahang (n = 176). SPSS software was used to analyse the descriptive statistics of the farmers' at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 111 publications
2
4
0
Order By: Relevance
“…The study's ndings clearly show a bipolar relationship between predictor factors with perceptions of bene t and risk, as Alhakimi and Slovic (1994) described [66]. Mustapa et al (2021) discovered that stakeholders' acceptance of new technology is signi cantly in uenced by high perceived bene ts and low perceived risks [67]. Therefore, the nding is further elucidated by previous studies, who showed an inverse relationship between general predictor factors such as belief in priorities, attitudes towards nature, and religion with perceptions of bene t and risk in determining the acceptance of Wolbachia and Outdoor Residual Spraying techniques [17,18].…”
Section: Direct Relationships Analysissupporting
confidence: 58%
“…The study's ndings clearly show a bipolar relationship between predictor factors with perceptions of bene t and risk, as Alhakimi and Slovic (1994) described [66]. Mustapa et al (2021) discovered that stakeholders' acceptance of new technology is signi cantly in uenced by high perceived bene ts and low perceived risks [67]. Therefore, the nding is further elucidated by previous studies, who showed an inverse relationship between general predictor factors such as belief in priorities, attitudes towards nature, and religion with perceptions of bene t and risk in determining the acceptance of Wolbachia and Outdoor Residual Spraying techniques [17,18].…”
Section: Direct Relationships Analysissupporting
confidence: 58%
“…The study's findings clearly show a bipolar relationship between predictor factors with perceptions of benefit and risk, as described by Alhakimi and Slovic [70]. Mustapa et al [71] discovered that stakeholders' acceptance of new technology is significantly influenced by high perceived benefits and low perceived risks. Therefore, the finding is further elucidated by previous studies, who showed an inverse relationship between general predictor factors such as belief in priorities, attitudes towards nature, and religion with perceptions of benefit and risk in determining the acceptance of Wolbachia and Outdoor Residual Spraying techniques [13,18].…”
Section: Direct Relationships Analysissupporting
confidence: 57%
“…Mustafa et al [31], in the study of the Malaysian environment, provide empirical support for an explanation of the predictors that influence farmers' attitudes toward adopting GM crops. This study reflects that Malaysian farmers display positive attitudes toward GM crops.…”
Section: Resultsmentioning
confidence: 99%
“…The institutional factors governing the activities involving GMOs have legal and administrative frameworks that provide rules, guidelines, and assistance [31]. As part of international trade agreements, many countries have agreed to protect seed companies' intellectual property rights through national legislation [35].…”
Section: Resultsmentioning
confidence: 99%